Impact of turnaround time on outcome with point-of-care testing for respiratory viruses: a post hoc analysis from a randomised controlled trial. Issue 2 (9th August 2018) - Brendish, Nathan J.; Malachira, Ahalya K.; Beard, Kate R.; Ewings, Sean; Clark, Tristan W.
Respiratory viruses are detected in around 40–50% of adults hospitalised with acute respiratory illness (ARI) [1, 2]. Routine laboratory PCR testing for respiratory viruses generally takes several hours to several days to generate results for clinicians and so cannot be used to inform decision making in real time. Decisions about hospitalisation, antibiotics, antivirals and side room isolation therefore need to be made presumptively and reviewed when results are available. Newer rapid molecular test platforms are accurate, easy to use, and generate a result in 1 h or less, making them potentially deployable for point-of-care testing (POCT) in clinical areas [3]. Recently, we reported on a large pragmatic randomised controlled trial (ResPOC) [4] which evaluated the impact of POCT (using the FilmArray Respiratory Panel (BioFire Diagnostics, Salt Lake City, UT, USA) which tests for a comprehensive range of viruses) in adults presenting to hospital with ARI. The study showed that POCT was associated with reductions in hospital length of stay overall and reductions in antibiotics use in patients with exacerbation of airways disease. Although this evidence would suggest that rapid molecular testing needs to be performed within clinical areas for these improved clinical outcomes, it has been suggested that rapid molecular test platforms used within centralised laboratories might also be associated with these clinical benefits, although the turnaround times (TATs) are likely to be much longer. In this follow-on study we evaluate the impact of POCT TAT on clinical outcomes with a view to determining how rapid molecular testing for respiratory viruses should be best implemented in clinical practice. As very rapid turnaround times lead to better outcomes, virus diagnostics should be performed at the point-of-care http://ow.ly/eD6p30koZGg